PENGUKURAN PRODUKTIVITAS ALUR PRODUKSI MENGGUNAKAN METODE LINE BALANCING DI PD SANDANG JAYA - Nurhasanah, Nunung; Simanjuntak, Jan Pratama (Industrial and Systems Engineering Assessment Journal (INASEA), 2012)
PD Sandang Jaya is a garment industry that produces products by order. PD Sandang Jaya realizes how important production processes to meet product demands and increase productivity. Thus, this research goal is to increase productivity by maximizing the existing production on production floor, so that the continuity of material flow can run smoothly in the production process. This research emphasizes on the production line which is always be an outstanding problem within the company. Line balancing method is used to improve the performance of any existing production process on the production floor by calculating the standard time and regulating the flow of production process on each line. By using Helgeson Birnie-line balancing method, the efficiency of production process increases to 90,38% and 9,62% for balanced delayed. By using Helgeson Birnie, each of production lines becomes more efficient. Some changes also occur in the Ws where Ws proposal is divided into three Ws. Ndeed, it will facilitate the flow of materials to make the process works. After calculating line balancing, labor allocation should be determine to decide quantity of total production. Total production obtained in this research is 113 units per day. Thus, total production for 30 days is 3.390 units or 282 dozen increasing from 3.000 units. Base on line balancing method, labor productivity increases from 214,8 to 250.